Strategi Pengumpulan Zakat Badan Amil Zakat Kota Padang - Ahmad, Fajri (Fakultas Dakwah dan Ilmu Komunikasi, 2020)
The purpose of this study is to determine the strategy of the Padang City Amil Zakat Institution in collecting zakat. The methodology used is field research using interview data, observation, and documentation. The results of the study explained that the Padang City zakat collection agency built tithe awareness for the people of Padang City. On the other hand, the community felt the presence of the Padang City Collection Agency. Through a work program: Padang smart, Religious, Prosperous, and Padang care which reaches all in Padang City. Zakat Collection Agency carried out a mapping strategy, built giver and receiver zakat communications, and opened grey/stands in shopping centres and government buildings. This strategy can increase the amount of zakat collected by the City of Padang Collection Agency.Keywords: Strategy, Zakat, Collection Agency.Tujuan penelitian ini untuk mengetahui strategi Lembaga Amil Zakat (Baznas) Kota Padang dalam memungut zakat. Metodologi yang digunakan ialah penelitian lapangan dengan metode pengumpalan data wawancara, observasi dan dokumentasi. Hasil penelitian menjelaskan bahwa Baznas Kota Padang membangun kesadaran berzakat bagi masyarakat Kota Padang. Pada sisi lain, masyarakat merasakan kehadiran Baznas Kota Padang melalui program kerja; Padang Cerdas, Padang Religius, Padang Sejahtera dan Padang Peduli yang menjangkau seluruh di Kota Padang. Baznas melakukan strategi pemetaan, membangun komunikasi Mustahiq-Muzakki, dan membuka gray/stand di pusat perbelanjaan dan gedung pemerintahan. Strategi ini mampu meningkatkan jumlah zakat yang dihimpun Baznas Kota Padang.Kata kunci: Strategi, Zakat Fitrah, Baznas.